DESIGN OF A HOMESTAY AREA IN HUTA HIGH REGENCY OF SAMOSIR REGENCY BASED ON BATAK TOBA LOCAL WISDOM - Asido Martodi Simbolon; Ramadhani Fitri; Novalinda (INFOKUM, 2022)
Indonesia is a country known for its rich natural and cultural resources. One of the tourism sectors in North Sumatra is the Toba Batak culture. Where one aspect of culture in the Toba Batak reflects the potential for cultural tourism in Huta Tinggi, Samosir Regency. To develop and advance the potential of the tourism sector, especially in Huta Tinggi, Samosir Regency, and also as an effort to preserve culture, a Homestay building is needed which is one of the important factors in the development of the Homestay area in Huta Tinggi, Samosir Regency. local wisdom with a modern form (Neo-Vernacular) Toba Batak. This is because Neo-Vernacular Architecture shows a modern form but still has the image or characteristics of the area, but with a touch that is in accordance with the context of today. In the context of realizing the Samosir Regency Vision "The Realization of a Prosperous, Independent, and Competitive Samosir Community Based on Tourism and Agriculture" then to achieve this the Samosir Regency government has made eight missions, two of which are; Development of environmental and cultural tourism as well as community empowerment as the main actors in the tourism business, and increasing the development of public facilities and infrastructure that support the tourism industry, smooth the economy and facilitate public services, one of the main elements of which is the preservation/conservation of all sites and tourist objects in the area. Samosir Regency. The research method in this design Determine the design topic, which in this case is the design of Homestay in Huta Tinggi, Samosir Regency Primary data collection is carried out by surveying the field to collect data needed in the design Questionnaireor questions about Homestay. Data analysis and the results of using the concept of a circulation plan the sopo in the form of a greenhouse sopo the concept of a meeting hall is formed from a perspective that raises the concept of the foundation pillars of a Batak Toba traditional house the concept an exhibition room By applying the concept of a mimetic theme in architecture, this homestay building in Huta Tinggi Regency, Samosir contains the typical characteristics of the Toba Batak culture which we know as the Tatak Toba traditional house (Rumah Bolon) along with the Batak gorga which is an attraction for visitors and with that we can introduce our culture to foreign tourists. educational f, informative, recreational as well as making visitors interested and comfortable visiting Samosir Regency and staying at a Homestay located in Huta Tinggi.